Enhanced Stability and Bioactivity of Natural Anticancer Topoisomerase I Inhibitors through Cyclodextrin Complexation - Víctor González-Ruiz; Ángel Cores; Olmo Martín-Cámara; Karen Orellana; Víctor Cervera-Carrascón; Patrycja Michalska; Ana I. Olives; Rafael León; M. Antonia Martín; J. Carlos Menéndez (MDPI AG, 2021)
The use of cyclodextrins as drug nano-carrier systems for drug delivery is gaining importance in the pharmaceutical industry due to the interesting pharmacokinetic properties of the resulting inclusion complexes. In the present work, complexes of the anti-cancer alkaloids camptothecin and luotonin A have been prepared with β-cyclodextrin and hydroxypropyl-β-cyclodextrin. These cyclodextrin complexes were characterized by nuclear magnetic resonance spectroscopy (NMR). The variations in the 1H-NMR and 13C-NMR chemical shifts allowed to establish the inclusion modes of the compounds into the cyclodextrin cavities, which were supported by docking and molecular dynamics studies. The efficiency of the complexation was quantified by UV-Vis spectrophotometry and spectrofluorimetry, which showed that the protonation equilibria of camptothecin and luotonin A were drastically hampered upon formation of the inclusion complexes. The stabilization of camptothecin towards hydrolysis inside the cyclodextrin cavity was verified by the quantitation of the active lactone form by reverse phase liquid chromatography fluorimetric detection, both in basic conditions and in the presence of serum albumin. The antitumor activity of luotonin A and camptothecin complexes were studied in several cancer cell lines (breast, lung, hepatic carcinoma, ovarian carcinoma and human neuroblastoma) and an enhanced activity was found compared to the free alkaloids, particularly in the case of hydroxypropyl-β-cyclodextrin derivatives. This result shows that the cyclodextrin inclusion strategy has much potential towards reaching the goal of employing luotonin A or its analogues as stable analogues of camptothecin.